Survey Role of Outsourcing in Nutrition Unit: Comparison of selected Hospitals with military Selected Hospitals in Tehran. - omid Khalilifar; bayram nejati zarnaghi; mohammad bakhtiari aliabad; ameneh valadkhani (Tehran University of Medical Sciences, 2015)
Background: Today, one of the effective ways of providing services is contracting with outside of organization and outsourcing. Objective: The current study aimed to investigate effect of outsourcing on performance of nutrition unit in studied hospitals. Methods: The current descriptive - analytical study performed in 2013, in two non-military hospitals and two military hospitals. 602 patients and 930 personnel were selected by simple randomized sampling. Data gathering performed by Patient and personnel satisfaction questionnaire, check list of kitchen's hygiene condition and check list of assessing the time spent by hospital manager for nutrition unit. Data on personnel cost were collected through accounting department. Data analysis performed by spss19 software. Findings: Patient and personnel satisfaction with food services of non-military specialized hospital (4.03±0.45) were more than military specialized hospital (p= 0/03 for patients & p= 0/021 for personnel) and in non-military general hospital were more military general hospital (p= 0/039 for patients & p= 0/028 for personnel). Hygiene condition of non-military hospitals kitchen was better than military hospitals, the time spent by hospital manager for nutrition affairs in military specialized hospital was 1.5 times more than non-military specialized hospital and in military general hospital it was 6.5 times more than non-military general hospital. Personnel cost in nutrition unit of military hospitals were 1.5 times more than non-military hospitals. Conclusion: Regarding the positive impact of outsourcing on performance of nutrition unit in hospitals, it is recommended that this strategy be applied in nutrition unit of military hospitals.